Complexities of Spiritual Care in Plural Societies : Education, Praxis and Concepts. - Grung, Anne Hege. (Berlin/Boston : Walter de Gruyter GmbH, 2022)
The interdisciplinary book series Studies in Spiritual Care publishes international research ranging from studies on specific aspects of Spiritual Care to programmatic contributions to the self-understanding of this new practice and research area. The series is of interest to professionals working in the field as well as to students and scholars.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books